ANALISIS PANGSA PASAR PRODUSEN TELEPON SELULER: : “APLIKASI MATRIKS MARKOV” (STUDI KASUS MAHASISWA IAIN PALOPO) - Arsyad Arsyad; Megasari Megasari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Cell phones are one of the most important communication tools in the current era of globalization. The rapid development of information and communication technology (ICT) is marked by the emergence of various brands of cellular phones that are produced in line with the high demand for cellular phones. This condition creates competition among cellular phone manufacturers to attract consumers and to maintain market share of their products. This study aims to analyze the current market share of smartphone manufacturers and predict smartphone brands in the future among IAIN Palopo students. This type of research is descriptive quantitative. Primary data was obtained from distributing questionnaires to 240 students from the 2017-2020 class. Data analysis using Markov chain method. The results of this study indicate: 1). The current market share of IAIN Palopo Student Smartphone brands are: Oppo 37.5%, Vivo 29.2%, Samsung 14.2%, Xiaomi 10%, Iphone 2.5%, and other brands 6.7%. 2). Predictions of the smartphone brand market share for IAIN Palopo students in the future (equilibrium conditions) are: Oppo 38.7%, Vivo 30.6%, Samsung 12.3%, Xiaomi 7.2%, Iphone 3.7%, and other brands 7.4%.